Exotic nation: Maurophilia and the construction of early modern Spain - Fuchs, Barbara (Univ. of Pennsylvania Press, 2009)
The quotidian and the exotic -- In memory of Moors : history, Maurophilia, and the built vernacular -- The Moorish fashion -- Playing the Moor -- The Spanish race -- Postscript : Moorish commonplaces